Case report: Preliminary study on the diagnosis and treatment of respiratory distress in patients with giant nodular goiter complicated with severe COVID-19 - Wang, Fang; Yu, Xing; Ren, Zhangxia; Wang, Yong (Frontiers in Medicine, 2023)
Background: To investigate the practicality of emergency surgical and conservative medical treatments in patients with giant nodular goiter complicated by severe coronavirus disease 2019 (COVID-19)-related respiratory distress,evaluate the prognosis based on the two interventions,and explore the diagnosis and treatment plan of COVID-19-related respiratory distress in patients with giant nodular goiter.Methods: Four cases were retrospectively collected.Among them,two cases underwent emergency surgery,one case was treated with conservative treatment,whereas the fourth case underwent emergency surgery after failure of conservative therapy.Results: Dyspnea was significantly improved postoperatively,and the endotracheal tube was successfully removed 10.5 h after the operation,but inflammatory markers were greatly enhanced as compared to the preoperative values,patients with different degrees of fever,cough,and other discomforts postoperatively.Case 1 showed complete remission of all symptoms after three weeks, while case 2 displayed fever,cough,drowsiness,and other symptoms after the discharge and was eventually readmitted..In case 3,the conservative COVID-19 treatment marginally improved the pulmonary infection,fever,and other symptoms,but cough and other discomforts were persistent,along with delirium in later stages.Moreover,case 4 reported extubation failure after undergoing treatment with the standard new coronary pneumonia regimen in the tracheal intubation state;however, the patient was successfully weaned and extubated nine days after emergency surgery to relieve the obstruction.Conclusions:Our preliminary exploration suggested that patients with giant nodular goiter and respiratory tract obstruction post-acute COVID-19 infection can undergo early surgery after surgical tolerance evaluation for a better prognosis.